Pergeseran Paradigma Pemidanaan bagi Tindak Pidana Korupsi Setelah Berlakunya Kitab Undang-Undang Hukum Pidana (KUHP) Nasional - Ade Kurnia; Harmelia, Harmelia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the paradigm shift in the criminalization of corruption crimes following the enactment of Law Number 1 of 2023 concerning the National Criminal Code (KUHP). The method used is normative law with a statutory and conceptual approach, to contribute to the strengthening of a just corruption criminalization system in Indonesia. The results of the study indicate that the reform of Indonesian criminal law through the enactment of Law Number 1 of 2023 concerning the National Criminal Code (KUHP) marks a significant new chapter in the history of the Indonesian criminal justice system. The new KUHP is not simply a legislative change, but rather a reflection of a comprehensive legal paradigm transformation, from a repressive and punitive approach to a more humanistic, restorative, and equitable one. In conclusion, the successful implementation of the KUHP does not depend solely on normative changes but must be accompanied by structural, cultural, and ethical reforms in law enforcement. Law enforcement officials are required to adapt to new perspectives, while the public needs to be educated that justice is not always synonymous with punishment. Socialization, legal education, and public participation are key to the successful internalization of restorative values at the community level. Thus, the National Criminal Code (KUHP) is a symbol of Indonesia's legal sovereignty and a commitment to building a criminal justice system that is adaptive, just, and grounded in the values ​​of Pancasila to ensure the protection and welfare of society as a whole. Keywords: Punishment Paradigm, Corruption Crime, National Criminal Code, Corruption Law, Criminal Law Reform.